The Custody of a Non-Muslim Mother of her Muslim Child at Al-Malikiya in Jordanian and Kuwaiti Personal Status Laws - Omar , Bassam Muhammad Qasim (Dirasat: Shari’a and Law Sciences, 2021)
This study aims to clarify the custody ruling of a non-Muslim mother for her Muslim son at Al-Malikiya in the Jordanian and Kuwaiti personal status laws, due to the importance of this topic. The study dealt with the concept of custody and its importance. The study followed the inductive approach to analyze the custody topic found in different sources and references, and reformulate them in accordance with the study objectives. It also used the deductive method to analyze statements and inferences, deduced from Fiqh texts. Additionally, it followed the comparative approach by comparing the opinions of Jurists among themselves and comparing between the Jordanian and Kuwaiti personal status laws. The study found that in case the parents are separated, Islam grants the right of custody to the mother. If the woman is a non-Muslim and based on the opinion of Al-Malikiya, there is no difference between a Muslim mother and a non-Muslim in the eligibility of the mother to have custody of her Muslim child. In addition, the cuddler should be with his mother, because her compassion and tenderness for him will be greater than others, even if the mother is not a Muslim. The research recommended the need to allocate a group of research papers related to the topic of custody in relation to emerging contemporary topics. Additionally, the need to revise some of the Personal Status Law texts because some of them did not discuss the topic of custody, while others were general.